A doação como instrumento de planejamento sucessório - SANTANA, Abraão de Carvalho (2023)
Succession Law regulates the sharing of property and inheritance, creating and modifying norms that are used in the course of succession, which only occurs with the death of the deceased, or when the death of the deceased is presumed. Thus, the hereditary right emerged and the alteration of whose by his successors in the legal relations in which he was part. The present work aims to deal specifically with succession planning, as well as its importance within inheritance law, analyzing it from the point of view of donation. For this, it is based on a bibliographic review, considering that, through this research technique, it is possible to recover knowledge already systematized in a certain area. In this sense, research was sought in legislation and doctrine that could support the discussion proposed here. In view of all that has been mentioned, it should be concluded that the donation institute, within civil legislation, must be seen as a legal instrument, which aims to assist in the implementation of succession planning. However, for this to become a reality, it is necessary that this instrument be handled correctly, within the legal boundaries in accordance with the doctrine and, also, in line with the jurisprudence. In this sense, it is also worth mentioning that the donation institute is one of the most effective instruments, since it is a type of contract provided for in the Civil Code of 2002, which means that the donation is an instrument arising from the will of the donor and the donee, of an agreement between them. And, generally, this contract consists of the assumption of an obligation by the donor, who commits to the delivery of the good that will be donated, and the reception of this good by the donee.